Gender, ethnicity, and landed property in Albania - Lastarria-Cornhiel, Susana; Sabates-Wheeler, Rachel; University of Wisconsin--Madison. Land Tenure Center. (Land Tenure Center, University of Wisconsin-Madison, 1998)
Methods used to privatize state property attest to Albania's commitment to a democratic and egalitarian society: farmland was distributed to the households working on the ex-collectives and state farms, and housing was sold at a nominal price to the families occupying it. There are social issues, however, that influence not only the potential role of property ownership in the development of a democratic society, but also the true workability of some persons' political and economic opportunities. This paper examines two of these social issues: gender and ethnicity. Assuming that property ownership is a necessary condition for establishing a democratic market economy, the potential denial to exercise those rights for a significant proportion of the population on the basis of gender or ethnicity could undermine Albania's attempts to establish a democratic society and dynamic market economy based on equal opportunity.
iv, 48 p.
Keywords: Right of property Social aspects Albania; Customary law Albania; Land tenure Social aspects Albania; Women Legal status, laws, etc. Albania; Ethnic groups Albania; Women farmers Albania; Albania Social conditions